HAND WEAKNESS IN CHARCOT-MARIE-TOOTH DISEASE 1X. (29th November 2012) - Arthur-Farraj, P; Murphy, S; Laura, M; Lunn, MP; Manji, H; Blake, J; Ramdharry, G; Fox, Z; Reilly, M
Abstract : There have been suggestions from previous studies that patients with Charcot-Marie-Tooth disease (CMT) have weaker dominant hand muscles. Since all studies to date have included a heterogeneous group of CMT patients we decided to analyze hand strength in 43 patients with CMT1X. We recorded handedness and the MRC scores for the first dorsal interosseus (FDIO) and abductor pollicis brevis (APB) muscles, median and ulnar nerve compound motor action potentials (CMAPs) and conduction velocities in dominant and non-dominant hands. Twenty-two CMT1X patients (51%) had a weaker dominant hand; none had a stronger dominant hand. Mean MRC scores were significantly higher for FDIO and APB in non-dominant hands compared to dominant hands. Median nerve CMAPs were significantly reduced in dominant compared to non-dominant hands. We conclude that the dominant hand is weaker than the non-dominant hand in patients with CMT1X. It has been suggested in previous studies that a difference in hand strength between dominant and non-dominant hands may suggest that overwork weakness causes increased muscle weakness as the dominant hand will be used more by the patient. Whether this extrapolation is valid remains to be seen but it is an important issue as exercise training to improve strength in CMT is a growing area of research. While our study does suggest that the dominant hand is weaker in patients with CMT1X, it would be premature to suggest this is due to overwork weakness.